Rola edukacyjna pomocy społecznej we wsparciu rodzin osób niepełnosprawnych psychicznie - Rajewska de Mezer, Joanna; Flaga, Ewa (Wydawnictwo Naukowe UAM, 2013)
Mental illnesses, mental deficiencies and other functional disorders of psychological nature call for care in different fields. The medical conditions cause deficiencies often connected with an inability to fulfill basic needs, protect one’s rights and control one’s behaviour. This can have tangible and intangible effects. People with mental disorders often face discrimination and social exclusion, which might cause their marginalization. Nowadays multifaceted support for people with the above disorders is emphasized in the field of welfare and in accessing a profes-sional role. However, people who live with a person with a developmental disability are still often forgotten. These are spouses or life partners of disabled persons, their adult or minor children, parents, distant relatives or friends. The situation of families of people with a devel-opmental disability and their individual members is often very difficult and requires a thor-ough diagnosis to provide competent support. Depending on the kind of illness or disorders and their etiology, the degree of mental deficiency of a family member, one’s age or significance and role in the family, work with the family can vary. The support can have a tangible or intangible character. It can be the social work with the family and professional psychological or legal counseling. This help is granted by social welfare bodies. Of prime significance are the educa-tion of the family, support in understanding the problem which they are experiencing and providing the necessary competence to offer help to the disabled person.
The role of education in social welfare support for families of mentally disabled people
Keywords: mentally disabled person; welfare; support; social welfare bodies; tangible or in-tangible benefits